ANALYSIS OF CEMENT BOND QUALITY USING CEMENT BOND LOG (CBL) AFTER SQUEEZE CEMENTING OPERATION IN THE PRODUCTION ZONE AT WELL X, INDONESIA - Kusuma, Wijaya
Carbon, capture, and storage (CCS) is a technology designed to reduce greenhouse gas emissions by capturing carbon dioxide (????????2) from large stationary sources, such as fossil fuel power plants, and storing it in a deep geological formation. In this study, the CCS program will be conducted at Well X, an abandoned exploration gas well, by converting it into a ????????2 injection well. Well X uses Portland cement, which is typically used in conventional oil and gas wells. Chemically, this cement is unstable in ????????2 rich environments. The cement sheath in the wellbore will be the first material exposed to the injected ????????2, so the quality of the cement bond needs to be considered. This study focuses on evaluating the quality of the cement bond based on the analysis of Cement Bond Log (CBL) dan Variable Density Log (VDL) data and the calculation of the bonding index (BI). The analysis is conducted on the production casing section (casing 9 5/8”) after squeezing program to improve the cement bond above the perforation zone. Squeeze cementing was performed at Well X in 2017. Squeeze cementing was conducted in 4 zones with different objectives. Zones 1 and 2 are in the casing 9 5/8” at depths of 538–540 m and 610–613 m, respectively. Analysis of the quality of cement bond after the squeezing program in zones 1 and 2 will be carried out qualitatively and quantitatively based on the minimum criteria and requirements that have been set. The qualitative and quantitative analysis of the cement evaluation after squeeze cementing shows that squeezing did not reduce the amplitude to a maximum of 10 mV and did not improve the cement bond according to the ????????2 injection well requirements. Additionally, the log interpretation results from VDL observed the presence of mikro-anulus in the injection zone. Squeeze cementing conducted on the 9 5/8” casing did not significantly change the quality of the cement bond. According to the established requirements, the squeeze cementing conducted did not meet the minimum cement quality qualifications for ????????2 injection purposes.